Metode Pembelajaran Mata Kuliah Audit: Apakah Sudah Relevan? - Saura, Renda; Dwiharyadi, Anda; Afni, Zalida (Journal of Applied Accounting And Business, 2023)
This study aims to determine the relevant learning methods used by tertiary institutions in the course audit course, which will produce graduates who have competencies that are in line with industry needs. This research focuses on identifying the learning methods currently applied by universities through semester plan learning (RPS) at various universities in Indonesia, which are obtained via the internet. As for identifying learning methods that can produce graduates who have competence in accordance with the industry, data is obtained through questionnaires distributed to accounting practitioners. This study applies a quantitative descriptive approach using survey methods. The population in this study were students majoring in accounting in Indonesia and practitioners in the fields of accounting, finance, and auditing. The results show that there is a gap between the learning methods currently applied by universities and those expected by practitioners. Higher education institutions mostly apply group discussions, while the industry applies case-based learning